2013
DOI: 10.1155/2013/154537
|View full text |Cite
|
Sign up to set email alerts
|

Residual Renal Function in Children Treated with Chronic Peritoneal Dialysis

Abstract: Residual renal function (RRF) in patients with end-stage renal disease (ESRD) receiving renal replacement therapy is defined as the ability of native kidneys to eliminate water and uremic toxins. Preserved RRF improves survival and quality of life in adult ESRD patients treated with peritoneal dialysis. In children, RRF was shown not only to help preserve adequacy of renal replacement therapy but also to accelerate growth rate, improve nutrition and blood pressure control, reduce the risk of adverse myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…We found a significantly higher rate of daily diuresis decline during the first year of follow-up in children with higher mean SBP values, with hypertension present in 90.9% and poorly controlled hypertension present in 63.6% of children who became anuric. Cross-sectional studies in pediatric patients showed a negative relationship between daily diuresis and blood pressure (2). In adult patients, the effect of hypertension and antihypertensive medications on preservation of RRF is not clear (12,21,23,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a significantly higher rate of daily diuresis decline during the first year of follow-up in children with higher mean SBP values, with hypertension present in 90.9% and poorly controlled hypertension present in 63.6% of children who became anuric. Cross-sectional studies in pediatric patients showed a negative relationship between daily diuresis and blood pressure (2). In adult patients, the effect of hypertension and antihypertensive medications on preservation of RRF is not clear (12,21,23,25).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous benefits from preservation of diuresis have also been shown in pediatric patients. Children with preserved RRF treated with PD are characterized by a faster growth rate, better nutritional status, reduced burden to the cardiovascular system, higher hemoglobin level, less severe disturbances of the calcium-phosphorus metabolism, and a lower risk of dialysis-related peritonitis (2). Recent data suggest that the rate of RRF decline is a more powerful prognostic factor than the baseline RRF, associated with mortality and technical failures in adult patients on long-term PD (3), and proteinuria together with baseline glomerular filtration rate (GFR) are independently related to the rate of RRF decline in adult continuous ambulatory PD (CAPD) patients (4).…”
mentioning
confidence: 99%
“…In clinical practice, it is considered synonymous with such parameters as daily diuresis and/or GFR. In patients with ESRD undergoing renal replacement therapy, these toxins are eliminated by dialysis or by native kidneys with preserved RRF (18). In theory, the preservation of native kidney function and the establishment of a higher baseline level of kidney function after transplantation in pre-emptive recipients will have important implications for the ongoing promotion of pre-emptive transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The highest score for each dimention was 6 and the scores for all the scales are 36. International Index of Erectile Function Inventory scoring for men was mild impotence (21-25), average impotence (16)(17)(18)(19)(20), advanced impotence (10-15) and severe impotence (5)(6)(7)(8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
“…In consequence, patients feel a lack of sexual attraction, as well as a drop in their performance and social interactions. It is therefore imperative to alleviate this problem (7).…”
Section: Introductionmentioning
confidence: 99%